Translanguaging as a decolonial pedagogic strategy for South African universities - Madiba, Mbulungeni (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
This article explores the persistent challenges posed by colonial pedagogies in South African universities, with a specific focus on the University of Cape Town (UCT). The imposition of colonial languages such as English and Afrikaans in South African universities has perpetuated a linguistic hierarchy wherein these two languages dominate, sidelining the indigenous African languages. Despite democratic changes in 1994, the continued dominance of the two colonial languages in teaching and learning reinforces a coloniality of language, knowledge, and power. In response to this, the article advocates for translanguaging as a decolonial pedagogy to disrupt existing power dynamics and promote linguistic inclusivity and justice in teaching and learning. The concept of translanguaging is introduced, and its potential as a transformative pedagogy for leveraging multilingual competence among students is explored. The article contends that translanguaging introduces a decolonial framework for learning and teaching for multilingual and multicultural students. An example from the University of Cape Town (UCT) is provided to demonstrate how translanguaging pedagogy can serve as a decolonial pedagogic strategy in the classroom. Methodologically, the study employed linguistic ethnography techniques to gather data. The data analysis illustrates the strategies employed by multilingual students to challenge and navigate the dominance of English academic language through the practice of translanguaging.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: Translanguaging; Decolonial pedagogic strategy; Linguistic repertoires; Coloniality of language; Language ideologies; Translanguaging (Linguistics); Culture -- Study and teaching; Education, Higher -- South Africa